High-intensity chemotherapy improved the prognosis of patients with high-grade B-cell lymphoma - Chen, Yanfang; Cai, Qing; Chang, Yu; Zhang, Mingzhi; Li, Zhaoming (Frontiers in Immunology, 2022)
Objective High-grade B-cell lymphoma (HGBL) is highly aggressive and has a poor prognosis. Methods The clinical data of 76 patients with High-grade B-cell lymphoma treated in our lymphoma center from July 2016 to April 2020 were analyzed retrospectively. The clinical features, treatment and prognosis of patients with two types of high-grade B-cell lymphoma were compared and analyzed. Results Among 76 patients with high-grade B-cell lymphoma, 44 cases (57.9%) were high-grade B-cell lymphoma, accompanied by MYC and Bcl-2 and/or Bcl-6 rearrangement (HGBLR) patients, and 32 cases (42.1%) were HGBL, NOS patients. The bone marrow infiltration, IPI (international prognostic index), Ann Arbor stage (III/IV), extranodal disease are more likely to occur in HGBLR group (P <0.05). Survival analysis of patients showed that overall survival (OS) and progression free survival (PFS) in HGBLR group were significantly shorter than those in HGBL, NOS group (median OS: 21 months vs not reached, P=0. 022; median PFS: 5 months vs 12 months, P = 0. 001). Further analysis demonstrated that, as compared with R-CHOP regimen, patients with HGBL who received high-intensity chemotherapy regimens (DA-EPOCH-R, R-CODOX-M/IVAC and R-Hyper-CVAD) had longer OS (median OS, 16 months vs not reached, P=0. 007) and PFS (median PFS, 5 months vs 11 months, P<0.001). Moreover, mu1tivariate ana1ysis showed that high-intensity chemotherapy regimens were independent risk factors for both PFS (P =0.001, HR: 0.306, 95% CI: 0.153–0.610) and OS (P =0.004, HR: 0.262, 95% CI: 0.105–0.656) in patients with HGBL. Conclusions HGBLR patients have worse prognosis than patients with HGBL, NOS. High-intensity chemotherapy may improve the prognosis of patients with HGBL.